2010
DOI: 10.1074/jbc.m110.135236
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive Post-translational Regulation of Plant Omega-3 Fatty-acid Desaturases Is Mediated by the Endoplasmic Reticulum-associated Degradation Pathway

Abstract: Changes in ambient temperature represent a major physiological challenge to membranes of poikilothermic organisms. In plants, the endoplasmic reticulum (ER)-localized omega-3 fatty-acid desaturases (Fad3) increase the production of polyunsaturated fatty acids at cooler temperatures, but the FAD3 genes themselves are typically not up-regulated during this adaptive response. Here, we expressed two closely related plant FAD3 genes in yeast cells and found that their enzymes produced significantly different amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 77 publications
(79 reference statements)
4
58
0
1
Order By: Relevance
“…cells other than those exhibiting high levels of ectopic [gene] expression and/or containing karmellae) were calculated and plotted as normalized GFP/rFP fluorescence ratios (±ca. standard deviations) according to O'Quinn et al 6 the results shown in (A-c) are representative of at least three independent experiments. ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 4 more Smart Citations
“…cells other than those exhibiting high levels of ectopic [gene] expression and/or containing karmellae) were calculated and plotted as normalized GFP/rFP fluorescence ratios (±ca. standard deviations) according to O'Quinn et al 6 the results shown in (A-c) are representative of at least three independent experiments. ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Addition of either the BF3 or TF3 N-terminal sequence to GFP-Cb5, however, resulted in enhanced protein degradation that was significantly inhibited by inclusion of MG132 (Fig. 1D and middle and right graphs), indicating the Fad3 N termini contain cis-acting signals that lumenal-targeted red fluorescent protein (RFP), 6 which serves as an internal control to normalize fluorescence values that may change due to variation in expression levels, plasmid copy number, etc., following biolistic bombardment. The degradation rates of each pair of co-expressed proteins (e.g., GFP-Cb5 and RFP-ER) were then calculated by measuring (via microscopy) the GFP/RFP fluorescence ratio in multiple, individually-transformed cells following inhibition of protein translation with cycloheximide.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 3 more Smart Citations